2009
DOI: 10.3855/jidc.535
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections due to leptospira, dengue and hepatitis E: a diagnostic challenge

Abstract: A case of mixed infection due to leptospira, dengue and hepatitis E is reported. Similar clinical presentation and simultaneous transmission of these diseases during rainy season can cause substantial misdiagnosis. Serological tests play a mainstay in diagnosis. Early detection by appropriate serological tests and institution of therapy is crucial and life saving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…On the other hand, concurrent infection of mosquito-borne disease with another waterborne disease, such as dengue fever and hepatitis A infection or malaria with typhoid fever, is quite often reported from different developing countries [26]. Also, co-infections due to Leptospira and HEV were reported from some tropical countries, but this is the first time the co-existence of YF with HEV as outbreaks in our African region was reported [27].…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, concurrent infection of mosquito-borne disease with another waterborne disease, such as dengue fever and hepatitis A infection or malaria with typhoid fever, is quite often reported from different developing countries [26]. Also, co-infections due to Leptospira and HEV were reported from some tropical countries, but this is the first time the co-existence of YF with HEV as outbreaks in our African region was reported [27].…”
Section: Discussionmentioning
confidence: 95%
“…Both of these diseases were often always discussed separately. However, leptospirosis and dengue coinfection is an extremely rare event, with only five cases previously [6][7][8][9] reported in the English medical literature.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature search revealed that only two such case of co-infection is reported so far. [12] Both the previous cases survived but our case died. We are reporting our case along with review and comparison of these three cases.…”
Section: Introductionmentioning
confidence: 62%
“…[1] Here we report a case where we detected dengue, leptospirosis and hepatitis E virus (HEV) triple co-infection. Extensive literature search revealed that only two such case of co-infection is reported so far.…”
Section: Introductionmentioning
confidence: 99%